Outcomes of the use of irrigating drains in severe odontogenic infection management - Prata-Júnior, Agnaldo Rocha; Takeshita, Wilton Mitsunari [UNESP]; de Oliveira Filho, Sérgio Alves (Elsevier, 2023)
Objective: This study aimed to evaluate the outcomes of 2 types of drains for severe odontogenic infection management. Study Design: Thirty-eight patients with severe odontogenic infections underwent drainage performed under general anesthesia. According to the type of drain used, they were randomized and separated into 2 groups: irrigating (n = 19) and non-irrigating drain (n = 19). Data such as age, ethnicity, sex, number of teeth, and fascial spaces were collected on admission through anamnesis. The clinical and laboratory parameters were checked every 24 hours until discharge. Symptom evolution was monitored daily using a visual analog scale. The Mann-Whitney U test was used for the primary outcome, and a P value < 0.05 was considered to indicate statistical significance. Results: No statistically significant difference in the overall length of stay was observed. Statistically significant differences in parameters such as pain, odynophagia, and leukocyte and segmented neutrophil counts were observed. Conclusions: Non-irrigating drains may be as effective as irrigating drains in treating severe odontogenic infections.